2021
DOI: 10.1371/journal.pone.0254013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water and fertilizer coupling on the physiological characteristics and growth of rabbiteye blueberry

Abstract: Understanding the impact of irrigation and fertilizer on rabbiteye blueberry (Vaccinium virgatum) physiology is necessary for its precision planting. Here, we applied varied irrigation and fertilizer under completely randomized experimental design to see its impact on the physiological characteristics and bush growth of rabbiteye blueberries. A comprehensive evaluation of the membership function was used to establish the best water–fertilizer coupling regimes. Rabbiteye blueberry enhanced the net photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
5
16
2
Order By: Relevance
“…Results showed that this species does not respond strongly to changes in fertilization levels in relation to Gs, with values between 200 and 300 mmol m −2 s −1 between treatments and evaluation seasons (p > 0.05). These results are in contrast to those found in a study carried out on blueberries, where Gs was affected by the fertilization doses together with the water regime, where a correlation was found between the fertilization dose and moisture content in the soil [44]. As the soil moisture was constant for all treatments in this study, it could be strongly influential so that no significant differences in Gs are observed between treatments [44].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results showed that this species does not respond strongly to changes in fertilization levels in relation to Gs, with values between 200 and 300 mmol m −2 s −1 between treatments and evaluation seasons (p > 0.05). These results are in contrast to those found in a study carried out on blueberries, where Gs was affected by the fertilization doses together with the water regime, where a correlation was found between the fertilization dose and moisture content in the soil [44]. As the soil moisture was constant for all treatments in this study, it could be strongly influential so that no significant differences in Gs are observed between treatments [44].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the application of compost to the soil increased levels of organic matter (OM) in all treatments (Tables 1 and 2), which could be affecting the moisture retention capacity, aeration, porosity, and soil carbon content as reported in multiple studies [45][46][47]. Said OM modifications in the soil could be having an impact not only on the physical parameters of the soil, but also to the nutritional status and biomass of the plant and consequently on the foliar area of the plant [44,45]. In the present study, the LAI was higher in both seasons in Q3 (Figure 2), showing an increase in the second season of more than 20% compared to CK and T1 (p < 0.05) and close to 10% higher than T3 (p < 0.05).…”
Section: Discussionmentioning
confidence: 76%
“…[ 36 ]. Evidence that appropriate water and fertilizer coupling regimes may improve the photosynthetic efficiency of plants and promote growth have been shown [ 37 ]. Therefore, choosing the appropriate nitrogen concentration may result in the enhanced drought resistance of plants [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous experimental results showed that both soil nutrients and moisture amounts influenced the increase in chlorophyll content of plants under water-deficient conditions (Wang et al 2021). Contrarily, the low amount of water had resulted in higher growth performance, several new shoots, chlorophyll content, and leaf soluble sugar compared with high amounts of water treatments (Guo et al 2021). Further, Basal and Szabo (2020) reported that irrigation regimes significantly altered the morpho-physiological traits.…”
Section: Introductionmentioning
confidence: 94%